Fiskalne aspekty polityki rolnej - Stulgis, Włodzimierz; Zawojska, Aldona (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1995)
Fiscal aspects of agricultural policy are mainly due to the redistributive and stimulative functions of the budget. Both these functions are examined considering agriculture as a whole, avoiding allocations within this sector and indicating the rising budget expenditure against social targets related to agricultural policy. Transformation of the system is accompanied by growing claims on government assistance, particularly as regards finances. Simplifying the problem it can be said that the budget itself does not produce. From the financial point of view it can be illustrated best by saying that economy is a system of communicating vessels. In some countries parliament debates on budget run according to the principle that indices for higher spending for a particular objective should be derived from indices of higher budget revenues or reduction of expenses for another objective. And thus the necessity for relative estimation of fiscal policy in the agricultural sector. It seems justified to relate the transfer of profits to agriculture - to GDP and the contribution of agriculture towards GDP. From the methodological point of view this is relativistic thanks to PSE and CSE indices. In OECD countries total transfers arc at the level of half of the agriculture contribution to GDP; achieved in Poland in the years 1992-1993 and what should be indicated with a tendency for gradual improvement.